PEMBERIAN VISTAMOV MENINGKATKAN PENGETAHUAN DAN KESIAPAN MENOLONG DRIVER OJEK ONLINE - Bagus Ananta; Ikhtiarni, Anggun; Setiyo Negoro, Muhamad Syamsul Arif (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
An accident is an event that injures individuals or makes the individuals die. Online drivers are vulnerable to traffic accidents while driving. Therefore, the implementation of (vistamov) educative videos about stabilization and movement could improve their cognition and readiness to provide first aid among online drivers. This research determined the influence of educative videos about stabilization and movement on the cognition and readiness of online drivers. This quantitative research applied a pre-experiment one-group pretest-posttest design. The applied sampling technique was proportionate stratified random sampling. The samples were 44 respondents according to the established inclusion and exclusion criteria. The instrument in this study used a knowledge and readiness to help questionnaire that had been tested for validity and reliability. The results showed the improved cognitive mean before and after the intervention, from 75.82 to 92.00. The mean of the driver’s readiness to provide first aid also improved from 73.76 to 85.45. The Wilcoxon test obtained a p-value of 0.0001 lower than 0.05. Thus, the implementation of the educative video was significant to improve the cognition and readiness to provide first aid among online drivers. The researcher recommends related institutions improve online drivers' readiness by promoting first-aid training.